Simple preparation and characterization of bismuth ferrites nanoparticles by thermal treatment method - Zahari, R. M.; Shaari, A. H.; Abbas, Z.; Baqiah, H.; Chen, S. K.; Lim, K. P.; Awang Kechik, M. M. (Springer, 2017)
In the present work, nanoparticles of multiferroic bismuth ferrites (BiFeO3) were synthesized via a simple thermal treatment method. BiFeO3 was prepared from an aqueous solution containing bismuth nitrate and iron nitrate as starting materials, polyvinyl pyrrolidone (PVP) as a capping agent and nitric acid to dissolve the bismuth nitrate, respectively. It is followed by thermal treatment at various calcination temperatures at 350, 450 and 550 °C. The samples were characterized by thermogravimetric analysis, X-ray diffractometer (XRD), transmission electron microscope (TEM), vibrating sample magnetometer and electron spin resonance (ESR) spectroscopy. XRD results indicate that the samples, calcined at 350, 450 and 550 °C, crystalized in rhombohedral crystal structure (space group R3c). The crystallinity of samples increased with increasing calcination temperature. Morphology study using TEM confirmed the growth of BiFeO3 nanoparticles with the average particle’s size increases from ~30 nm up to ~80 nm with the increasing of calcination temperature from 350 to 550 °C. Magnetic saturation Ms, of samples decreased from 2.15 to 0.25 emu/g while the coercivity Hc, increased from 54.41 to 272 G when the calcination temperature increased from 350 to 550 °C. ESR revealed increment of g-factor value from 2.14 to 2.64 and peak-to-peak linewidth from 129.33 to 201.61 Oe with the increasing of calcination temperature from 350 to 550 °C. The results demonstrate that by using thermal treatment method, the BiFeO3 nanoparticles can be obtained at low temperature, i.e. 350 °C.